Lymphogranuloma Venereum Presenting as a Rectovaginal Fistula - C. M. Lynch; T. L. Felder; R. A. Schwandt; R. G. Shashy (Hindawi Limited, 1999)
Lymphogranuloma venereum (LGV) is a rare form of the sexually transmitted disease caused by Chlamydia trachomatis. In the United States, there are fewer than 350 cases per year. In a review of the world's literature, there has not been a case reported in the last thirty years of a case ofLGV presenting as a rectovaginal fistula. We present a case of an otherwise healthy American woman who presented with a rectovaginal fistula. Although uncommon, LGV does occur in developed countries and may have devastating tissue destruction if not recognized and treated before the tertiary stage. Infect. Dis. Obstet. Gynecol. 7:199-201, 1999.